Proposal for an approach to evaluate continuity in service supply chains: Case of the Moroccan electricity supply chain - Houda Mezouar; Abdellatif El Afia (Institute of Advanced Engineering and Science, 2019)
The purpose of this paper is to develop an approach to analyse and evaluate continuity in Service Supply Chain (SSC), through a case study. This approach is based on the data-driven quality strategy